Enhancing H2 evolution performance of an immobilised cobalt catalyst by rational ligand design1. Issue 5 (20th May 2015) - Willkomm, Janina; Muresan, Nicoleta M.; Reisner, Erwin
<x xml:space="preserve">Abstract</x> Rational ligand design was employed to improve the proton reduction activity of an immobilised cobalt diimine–dioxime catalyst.